2004
DOI: 10.1177/08830738040190070401
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid—Induced Pancreatitis in Childhood Epilepsy: Case Series and Review

Abstract: In the past 6 years, 11 children on valproic acid have developed pancreatitis in our children's hospital. Valproic acid has been used as one of the primary anticonvulsants for generalized seizures in children for the past 25 years. A literature review reveals mostly singular reports of pancreatitis over the past decade. The charts of the 11 patients with valproic acid-induced pancreatitis were reviewed. Dosage, valproic acid serum levels, duration of therapy, and concomitant medications were examined. Families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 18 publications
1
27
1
1
Order By: Relevance
“…In belong others articles have been published on this theme, followed by numerous reports (11)(12)(13)(14) and case control to establish, certainly, that VPA may cause the AP (15). Some authors have suggested that the problem of the risk AP VPAinduced may be more common than thought, pointing out that the risk increases after the first year of therapy and that its suspension causes a resolution of the symptoms(16).…”
Section: Discussionmentioning
confidence: 99%
“…In belong others articles have been published on this theme, followed by numerous reports (11)(12)(13)(14) and case control to establish, certainly, that VPA may cause the AP (15). Some authors have suggested that the problem of the risk AP VPAinduced may be more common than thought, pointing out that the risk increases after the first year of therapy and that its suspension causes a resolution of the symptoms(16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dose, duration of treatment, serum valproic acid levels, generic preparation, and the presence of concomitant antiepileptic drugs have not shown any implication in causing pancreatitis. [15][16][17] Altered renal function test with raised serum creatinine of 6.4mg/ dl and urea of 126mg/dl in our patient with previously normal renal function could be due to contrast used for CECT -contrast induced nephropathy, although AP could also be attributable.…”
Section: Figure 1 Ct Section Showing Necrotizing Pancreatitismentioning
confidence: 69%
“…Sinclair notified 2 such cases in 5 and 8 years old child in her 11 case series of VPA associated pancreatitis in pediatric age group. 16 Younger age group and first year of initiation of treatment have been determined as risk factors for VPA associated pancreatitis. In most patients, early discontinuation of the drug resulted in successful resolution of the symptoms, as was in our case.…”
Section: Figure 1 Ct Section Showing Necrotizing Pancreatitismentioning
confidence: 99%
“…But this mitochondrial b-oxidation enzyme deficient theory was challenged by other workers who did not find any change in amino acid levels responsible for VPA induced pancreatitis 9 . The diagnosis of pancreatitis is made on clinical findings 10 as well as increase in serum amylase and lipase values 11 . Abdominal ultrasound is useful in the preliminary evaluation of patients suspected of having acute pancreatitis and it should be done in the first 24-48 hours from the onset of the clinical symptoms 12 as was done in the present case.…”
Section: Discussionmentioning
confidence: 99%